Process integrated biosensors for real-time monitoring of antibodies for automated affinity purification. Issue 44 (31st October 2022) - Tran, Thuy; Martinsson, Erik; Gustavsson, Robert; Tronarp, Otto; Nilsson, Mats; Hansson, Kristoffer Rudenholm; Lundström, Ingemar; Mandenius, Carl-Fredrik; Aili, Daniel
Abstract : A sensor technology for in-line detection of monoclonal antibodies (mAbs) in affinity capture steps is demonstrated. Continuous mAb monitoring during multiple consecutive purification cycles can facilitate automatization and continuous processing. Abstract : Therapeutic monoclonal antibodies (mAbs) provide new means for treatments of a wide range of diseases and comprise a large fraction of all new approved drugs. Production of mAbs is expensive compared to conventional drug production, primarily due to the complex processes involved. The affinity purification step is dominating the cost of goods in mAb manufacturing. Process intensification and automation could reduce costs, but the lack of real-time process analytical technologies (PAT) complicates this development. We show a specific and robust fiber optical localized surface plasmon resonance (LSPR) sensor technology that is optimized for in-line product detection in the effluent in affinity capture steps. The sensor system comprises a flow cell and a replaceable sensor chip functionalized with biorecognition elements for specific analyte detection. The high selectivity of the sensor enable detection of mAbs in complex sample matrices at concentrations below 2.5 μg mL −1 . In place regeneration of the sensor chips allowed for continuous monitoring of multiple consecutive chromatographic separation cycles. Excellent performance was obtained at different purification scales with flow rates up to 200 mL min −1 . This sensor technology facilitates efficient column loading, optimization, and control of chromatography systems, which can pave the way for continuous operation and automation of protein purification steps.